Evaluation of Nigeria’s Energy Policy on Biomass Utilization - Mohammed, Nabilah Sani; Hamdan, Mahani (CV. Literasi Indonesia, 2024)
Biomass energy, employed for centuries as a fuel in developing nations, stands as the longest-standing energy source still actively employed by humans today. Nigeria has an abundance of different biomass energy sources, with many of them remaining untapped and undeveloped across various levels. Despite its widespread availability throughout the nation, policies aimed at enhancing its utilization have received limited attention. Several obstacles hindering Nigeria's adoption of biomass energy need to be eliminated for it to develop to reach the levels observed in some developed nations. This paper examined empirical studies to assess the factors that shape the Nigerian biomass energy adoption and policies. The study explored a total of 16 articles on biomass utilization and summative content analysis was used to analyze them. The results indicate that political, economic, and technological factors have influenced Nigeria's biomass energy adoption and policy. This calls for a need to address these multifaceted challenges to promote the sustainable use of biomass as an energy source. This aligns with the seventh goal of the United Nations (UN) Sustainable Development Goals (SDGs), emphasizing affordable and clean energy.